Hubungan Sikap, Perilaku, dan Dukungan Keluarga dengan Tanda dan Gejala Keputihan Patologis pada Remaja Putri - Putri Trifirdiana; Nedra Wati Zaly (Universitas Baiturrahim, 2026)
Introduction: Adolescence is a transitional stage from childhood to adulthood. When a teenage girl experiences menstruation, it indicates that her reproductive organs are functioning properly. Therefore, maintaining genital hygiene is essential to prevent reproductive health problems, such as vaginal discharge. For this reason, what you must have is good attitudes, behavior, and family support regarding vulva hygiene to achieve reproductive health for teenagers. Purpose: This research aims to identify the relationship between attitudes, behavior, and family support on signs and symptoms of vaginal discharge. Method: This study employed a quantitative research design using an analytic cross-sectional approach. The population consisted of tenth-grade female students of SMK Kesehatan Annisa. The sample comprised 83 respondents, selected using a simple random sampling technique. Results: The results of this study showed that 56 respondents (67.5%) did not experience signs and symptoms of vaginal discharge, 77 respondents (92.8%) had a positive attitude, 73 respondents (88.0%) had positive behavior, and 44 respondents (53.0%) had family support the good one. The results of the bivariate research showed no relationship between attitudes and signs and symptoms of vaginal discharge, with a value of 0.084. Conclusion: There was no correlation between behavior and signs and symptoms of vaginal discharge, with a value of 0.304. There was no correlation between family support and signs and symptoms of vaginal discharge, with a value of 0.402. It is recommended that future researchers conduct research using supporting examinations for more accurate results.